Penilaian pandangan pelajar ke atas perbezaan layanan ibu bapa terhadap anak lelaki dan anak perempuan - Mohamad Nasir Saludin,; Rika Fatimah, P.L.,; Naziren Nazarudin, (2008)
It is interesting to discuss point of view of student on social issues such as the differences of attention of parents towards the sons and daughters. The study on the view of student is important by considering that the student themselves have double role for not only as knowlegeable who are assessing their social environment but also as sons or daugthers with regards to their own parents. In the other hand, it is quite complex and subjective to asses the differences of attention of parents towards the sons and daughters since there is no standard measurement to assess student’s point of view on the differences of attention of parents towards the sons and daughters. Therefore, this study offered a discussion on the application of Fuzzy Logic Controller (FLC). FLC is flexible enough to be applied since it is able to simplfy high complexity and subjective matters to be much easier to understand. Based on literature review, we identify several dimensions and variables that being used in this study. In addition, this study also has examined how far the differences between the behavior or attention to their daughters. In overall the result suggested that, there are inconspicuous differences between the behavior or attention of parents to their sons and daughters. Although for each dimesions, we found differences between the behavior or attention of parents to their sons and daughters